The role of cultural dimensions in shaping governance practice in non-profit organizations - Alnameh, Abdullh H; Zakariyah, Habeebullah (Universiti Teknologi MARA Selangor, 2025)
In recent years, global financial crises have unveiled significant vulnerabilities within the governance structures of financial institutions, including non-profit organisations. Given that these organisations often possess extensive financial resources and perform vital roles in society, there exists an urgent imperative to cultivate robust governance mechanisms that ensure their accountability and transparency. However, a thorough review of the existing literature indicates an obvious lack of attention to the influence of cultural factors on governance mechanisms and processes within non-profit organisations, despite their increasing globalisation. To bridge this critical gap in research, this study utilises Hofstede’s cultural dimensions as a framework to investigate how cultural values shape the governance mechanisms of non-profit organisations, particularly focusing on three key governance aspects related to the board of directors. Qatar serves as the specific context for this investigation, owing to the unique socio-political and cultural characteristics of the country. This study employs a qualitative research design, with data gathered through semi-structured interviews with board members of non-profit organisations in Qatar, all of whom possess relevant experience in the sector. The findings reveal that cultural values play a pivotal role in shaping the governance structures of non-profit organisations, particularly within the targeted governance mechanisms. This study not only extends our understanding of cultural influences on governance within the Gulf Cooperation Council (GCC) countries but also provides vital recommendations for policymakers and practitioners aimed at enhancing governance systems in culturally diverse societies.